2015
DOI: 10.1111/jonm.12309
|View full text |Cite
|
Sign up to set email alerts
|

Professional practice models for nursing: a review of the literature and synthesis of key components

Abstract: This summary of published professional practice models provides a guide for nurse leaders who seek to develop a professional practice model. The essential elements of a professional practice model; theoretical foundation and six common components, are clearly described. These elements can provide the starting point for nurse leaders' discussions with staff to shape a professional practice model that is meaningful to direct care nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(117 citation statements)
references
References 58 publications
1
106
0
6
Order By: Relevance
“…When comparing our model to other published nursing PPMs, similar components were identified despite the varying language used [9, 22, 29]. A review of the literature by Slatyer et al [22] identified six key concepts that were present in all of the studies reviewed.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…When comparing our model to other published nursing PPMs, similar components were identified despite the varying language used [9, 22, 29]. A review of the literature by Slatyer et al [22] identified six key concepts that were present in all of the studies reviewed.…”
Section: Discussionmentioning
confidence: 66%
“…A review of the literature by Slatyer et al [22] identified six key concepts that were present in all of the studies reviewed. The concepts were leadership; nurses' independent and collaborative practice; environment; nurse development and recognition; research/innovation; and patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central importance of nurses having autonomy and control over their practice is emphasized in Magnet Recognition programmes and PPMs (Slatyer et al., ). In this study nurses' control over practice was measured using the CONP scale, and CA and COUO subscales (Parsons & Murdaugh, ), which have acceptable psychometric properties.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in this field of nursing indicate these models are an appropriate response to the demands of the global agenda (6), and to the development of leadership required by the profession (7). They are a way of articulating the practice of nursing with the health system (8), complementing the theoretical development of other levels in the knowledge hierarchy (9,10), and responding to the highest accreditation criteria, while allowing for a link between the academy and assistance (11), generating an impact on nursing practice (12).…”
Section: Introductionmentioning
confidence: 99%